New Trends in Computational Electromagnetics - Ozgur Ergul, Ergul (Electromagnetics and Radar, 2020)
Computational electromagnetics is an active research area concerned with the development and implementation of numerical methods and techniques for rigorous solutions to physical problems across the entire spectrum of electromagnetic waves - from radio frequencies to gamma rays. Numerical methods and techniques developed and implemented in this area are now used every day to solve complex problems in diverse application areas, including but not limited to antennas, telecommunications, biomedical imaging, sensing, energy harvesting, nanotechnology, and optics. The purpose of this book is to provide a broad overview of the recent efforts in computational electromagnetics to develop and implement more robust, stable, accurate, and efficient algorithms. After an extensive overview of the main trends in computational electromagnetics, individual chapters written by international experts explore the state-of-the-art in frequency-domain surface integration; frequency-domain volume integral equations; time-domain integral equations; time-domain methods for plasmonic media; finite element methods; geometric modelling and discretization for integral equations; hierarchical vector basis functions; analysis of electromagnetic fields in multilayered media; acceleration and parallelization techniques; periodic problems and determining related eigenvalues; algebraic preconditioning; high-frequency techniques and hybridizations; and uncertainty quantification for large-scale electromagnetic analysis.